Analisis Penyimpangan Asas Itikad Baik Dalam Perjanjian Sewa Menyewa Kendaraan Di Kota Pontianak Kalimantan Barat - Romadhon, Dimas Dzuhri; Soedagoeng, Gembongseto Hendro; Lestari, Nina Niken (Faculty of Law, Universitas Muhammadiyah Pontianak, 2024)
Vehicle leasing agreements in Pontianak City, West Kalimantan often cause legal problems, especially in relation to deviations from the principle of good faith as stipulated in Article 1338 paragraph (3) of the Civil Code. This principle requires each party to the agreement to carry out obligations honestly, fairly, and in accordance with the norms of decency prevailing in the community. This research aims to identify concrete forms of deviation from the principle of good faith in the practice of vehicle leasing and analyze its legal impact on the relationship between business actors and consumers. This research uses an empirical method with a socio-legal approach, and data collection is carried out through interviews with vehicle rental business owners and consumers who have suffered losses. The results showed that deviations occurred at the stages before, during, and after the implementation of the agreement, with forms such as embezzlement of vehicles, use of vehicles for criminal acts, late returns, and dishonest utilization of contract concessions. These deviations cause financial losses, legal uncertainty, and decreased trust between parties. Therefore, it is necessary to increase legal awareness, formulate more detailed and firm contracts, and equal legal protection for both parties in order to enforce the principle of good faith in every vehicle rental transaction.